Nugget Tahu Dan Nangka Muda (Artocarpus Heterophyllus) Sebagai Alternatif Makanan Siap Saji Rendah Lemak Dan Protein Serta Tinggi Serat - Mohammad Nurul Hidayatullah (LPPM Politeknik Pratama, 2023)
Nuggets are processed meat flakes which are shaped in such a way with the addition of certain ingredients to form a new product that is accepted by the public. The aim of this study was to determine the effect of the proportion of tofu and young jackfruit on the physical, chemical and organoleptic characteristics of the nuggets. The design of this study was a completely randomized design (CRD) with five treatments and three replications. The treatments used were tofu and young jackfruit ratios, including 100:0, 85:15, 80:20, 75:25 and 70:30. Data were analyzed using Anova, if the number of Fcount was greater than or equal to Ftable, further testing was carried out using DNMRT at a level of 5%. The results of Anova showed that the ratio of tofu and young jackfruit had a significant effect on protein content, fiber content, and hedonic sensory assessment of aroma, firmness, taste, and overall nugget assessment. The ratio of tofu and young jackfruit had no significant effect on the moisture content of the nuggets. The best treatment was the ratio of tofu and young jackfruit 80:20 with a water content of 57.13%, protein 9.64%, crude fiber 1.23%, and hedonic assessment of aroma, elasticity, taste, and the overall rating was somewhat favored by panelists